BIOREMEDIATION OF CLAY SOILS IMPACTED BY PETROLEUM - Pala, Danielle Marins; Freire, Denize Dias de Carvalho; SantAnna Jr., Geraldo Lippel (Revista de Engenharia Térmica, 2002)
The application of bioremediation processes in recuperating contaminated sites is gaining ground, due to its efficiency in removing a number of different classes of contaminants and its cost, which tends to be lower than that of other technologies. In this work, the influence of some factors that are important for the biodegradation of the petroleum present in clay soil was studied. Experiments were conducted using two types of reactor, a slurry-phase reactor and a fixed bed reactor. The processes employed were shown to be highly effective in decontaminating the soil, achieving removal rates of around 80%.